(untitled) (Pedagogy of Higher and Secondary Education, 2006)
Methodological culture ofa music teacher with respect to humani:anon of education. The article deals with the goals, content structure ofthe integratedcourse “Methodology ofarts education", that prepares mastersforpedagogical activities in universities. It shapes the ability to integrate arts education with achievements of similarsciences and to get the wttm ofarts education activities as a unite and systematic process.